Anesthesia and analgesia for experimental craniotomy in mice and rats: a systematic scoping review comparing the years 2009 and 2019 - King, Hannah; Reiber, Maria; Philippi, Vanessa; Stirling, Helen; Aulehner, Katharina; Bankstahl, Marion; Bleich, André; Buchecker, Verena; Glasenapp, Aylina; Jirkof, Paulin; Miljanovic, Nina; Schönhoff, Katharina; et al. (Frontiers in Neuroscience, 2023)
Experimental craniotomies are a common surgical procedure in neuroscience. Because inadequate analgesia appears to be a problem in animal-based research, we conducted this review and collected information on management of craniotomy-associated pain in laboratory mice and rats. A comprehensive search and screening resulted in the identification of 2235 studies, published in 2009 and 2019, describing craniotomy in mice and/or rats. While key features were extracted from all studies, detailed information was extracted from a random subset of 100 studies/year. Reporting of perioperative analgesia increased from 2009 to 2019. However, the majority of studies from both years did not report pharmacologic pain management. Moreover, reporting of multimodal treatments remained at a low level, and monotherapeutic approaches were more common. Among drug groups, reporting of pre- and postoperative administration of non-steroidal anti-inflammatory drugs, opioids, and local anesthetics in 2019 exceeded that of 2009. In summary, these results suggest that inadequate analgesia and oligoanalgesia are persistent issues associated with experimental intracranial surgery. This underscores the need for intensified training of those working with laboratory rodents subjected to craniotomies. Systematic review registration https://osf.io/7d4qe.